2015
DOI: 10.1007/s12072-015-9641-1
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-induced acute kidney injury in patients with cirrhosis

Abstract: Acute kidney injury (AKI) is a common and life-threatening complication in patients with cirrhosis. Recently, new criteria for the diagnosis of AKI have been proposed in patients with cirrhosis by the International Club of Ascites. Almost all types of bacterial infections can induce AKI in patients with cirrhosis representing its most common precipitating event. The bacterial infection-induced AKI usually meets the diagnostic criteria of hepatorenal syndrome (HRS). Well in keeping with the "splanchnic arterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 44 publications
1
30
0
1
Order By: Relevance
“…Assuming a response rate in terlipressin as 56% and in noradrenaline as 43%, and a 10% noninferiority margin, with an alpha error of 5% and power of 80%, we needed to enroll 57 cases in each arm. (21,22) Statistical analyses were performed using SPSS software (version 20.0; IBM Corp., Armonk, NY). Patient clinical and biochemical indices are expressed either as mean ± SD or median (interquartile range; IQR).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming a response rate in terlipressin as 56% and in noradrenaline as 43%, and a 10% noninferiority margin, with an alpha error of 5% and power of 80%, we needed to enroll 57 cases in each arm. (21,22) Statistical analyses were performed using SPSS software (version 20.0; IBM Corp., Armonk, NY). Patient clinical and biochemical indices are expressed either as mean ± SD or median (interquartile range; IQR).…”
Section: Discussionmentioning
confidence: 99%
“…All authors had access to the study data and reviewed and approved the final manuscript. Assuming a response rate in terlipressin as 56% and in noradrenaline as 43%, and a 10% noninferiority margin, with an alpha error of 5% and power of 80%, we needed to enroll 57 cases in each arm …”
Section: Methodsmentioning
confidence: 99%
“…Secondly, elimination of certain molecules can be affected by renal failure and also renal replacement therapy. Acute kidney injury (AKI) is frequent in patients with cirrhosis, especially in bacterial infections[11]. While CRP has a high molecular weight (MW) (115-kDa) and its renal clearance is negligible[12,13], PCT is small with a MW of 13 kDa, and renal elimination is thought to be one of the major pathways for its elimination[14].…”
Section: Introductionmentioning
confidence: 99%
“…Much evidence from previous studies suggested that SIRS had a negative effect on the outcome of cirrhotic patients. It was indicated that SIRS correlated with portal hypertension‐related bleeding, acute renal function deterioration, HE, and even extra‐hepatic organ failure. The pathogenic explanation may be cytokine synthesis and release in patients with SIRS, which leads to derangement of systemic and renal hemodynamics that may end in hepatorenal syndrome .…”
Section: Discussionmentioning
confidence: 99%
“…21 The presence of SIRS at admission affected both the liver and kidney function, 22,23 and could predict the development of ARF and severe hepatitis. 17 Acute renal function failure is one of the most serious complications of SIRS and was strongly associated with organ failure. 10,24 In our study, Cr ≥175 μmol/L was shown to be an independent risk factor for 90-day mortality (HR = 2.768; CI, 1.53-5.04; P = 0.001).…”
Section: Discussionmentioning
confidence: 99%